Venomous spiders of Albania –does an increase of temperature influence the toxicity of spider venom?. (September 2022) - Vrenozi,; Blerina,
Abstract: Black widow spiders ( Latrodectus sp.) are distributed worldwide, and in Albania the L. tredecimguttatus Rossi, 1790 has been the dominant spider. Other medically important spiders in Albania include the brown recluse with symptoms known as loxoscelism, the false black widow and the egg sac spiders; the last two inducing similar symptoms to a wasp sting. Methods: The data analyzed is from a decade-long study of 125 patients hospitalized in the regional hospital of Fier County, in the Western Lowland of Albania from May 2009 and to October 2018. Objective: Although the venom is rarely fatal, the recent spider bites raise questions about the influence of higher air temperatures on their possibly increased toxicity. Results: Significantly the severity of the α-latrotoxin rises during the summer, when human–spider contact frequency is higher and when the black widow spiders have an increased motivation to protect their egg sacs. Conclusion: This study revealed an increased severity of the black widow bites with respect to patient health, shown via all the severe systemic symptoms, during those months with higher temperatures. Graphical abstract: Image 1 Highlights: The spider bites revealed a higher venom severity during summer, when there was a higher human-spider contact frequency. The longer recovery times are probably related to the quantity and toxicity of the spider venom á-latrotoxin. Extreme environmental conditions increase the spider motivation to protect the egg sac and self-protect. Higher environmental temperatures may thus lead to higher black widow venom toxicity during the hot summer months.